2007
DOI: 10.1186/1472-6807-7-57
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the second bromodomain of Brd2 and its specific interaction with acetylated histone tails

Abstract: Background: Brd2 is a transcriptional regulator and belongs to BET family, a less characterized novel class of bromodomain-containing proteins. Brd2 contains two tandem bromodomains (BD1 and BD2, 46% sequence identity) in the N-terminus and a conserved motif named ET (extra Cterminal) domain at the C-terminus that is also present in some other bromodomain proteins. The two bromodomains have been shown to bind the acetylated histone H4 and to be responsible for mitotic retention on chromosomes, which is probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 49 publications
6
58
1
Order By: Relevance
“…1B), indicating that integrity of the bromodomains is essential for this function. Similarly, a double Brd2 mutant with point mutations Y152K and N428A in BD1 and BD2, respectively, previously shown to affect Brd2 functionality (Huang et al, 2007;Nakamura et al, 2007), did not associate to mitotic chromosomes (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B), indicating that integrity of the bromodomains is essential for this function. Similarly, a double Brd2 mutant with point mutations Y152K and N428A in BD1 and BD2, respectively, previously shown to affect Brd2 functionality (Huang et al, 2007;Nakamura et al, 2007), did not associate to mitotic chromosomes (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…While single bromodomains from Brd2 have been shown to attach to histone peptides in vitro (Huang et al, 2007;Nakamura et al, 2007;Umehara et al, 2010a;Umehara et al, 2010b), we have observed chromosome dissociation of a construct encompassing both intact bromodomains in the cell, highlighting the relevance of other structural characteristics in the context of the full-length protein for chromatin association in vivo. In this regard, motif B seems to be specifically required for chromosome association, since deletions of similar extent, N-terminal or Cterminal to motif B, do not affect Brd2 behavior or function.…”
Section: Role Of Motif B In Chromatin Recognitionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, the bromodomains of BRD2 have been shown to bind acetylated histone H4 at lysine 12 (H4K12 ac ) in cells [37]. A dissociation constant (K D ) of 360 lM for the di-acetylated substrate peptide H4K5 ac /K12 ac has been determined in vitro by SPR [36] and a K D for the mono-acetylated H4K12 ac peptide of 2.9 mM has been determined by NMR titrations [38]. Furthermore, closely spaced multiple acetylation sites have been shown to increase affinity of the H4 tail for the murine BET family member BRDT [39] and this observation has been studied in detail for the entire subfamily of BET proteins [33] suggesting a cooperative role of neighbouring sites for substrate binding.…”
Section: Bromodomain Substratesmentioning
confidence: 99%
“…Most importantly BET proteins have been shown to bind to multiple adjacent acetyl sites with increased affinity and the structural basis of this interaction has been explained in detail in the case of the [82] murine BRDT [39] and the human BRD4 [33]. Tetra-acetylated histone H4 peptides (K5 ac /K8 ac /K12 ac /K16 ac ) have single digit micromolar affinity for single or tandem BET BRDs and both bromodomains of each BET member exhibit affinity for histone H4 peptides with single or multiple acetylations although the Nterminal domain in each protein seems to bind with higher affinity than the C-terminal one [33,[36][37][38][39]45,49]. Affinity for histone H3 peptides has also been demonstrated although it appears to be systematically stronger in the case of the C-terminal domains suggesting a mode of cooperativity between the tandem modules, either binding to the same nucleosome on different histone tails at the same time, or bridging adjacent nucleosomes by binding on histone H3 of the first and histone H4 of the second.…”
Section: Bromodomain Substratesmentioning
confidence: 99%